Corticotropin-Releasing Factor Receptors Modulate Oxytocin Release in the Dorsolateral Bed Nucleus of the Stria Terminalis (BNST) in Male Rats - Martinon, Daisy; Dabrowska, Joanna (Frontiers in Neuroscience, 2018)
The neuropeptide oxytocin (OT) plays an important role in the regulation of social and anxiety-like behavior. Our previous studies have shown that OT neurons send projections from the hypothalamus to the dorsolateral bed nucleus of the stria terminalis (BNSTdl), a forebrain region critically involved in the modulation of anxiety-like behavior. Importantly, these OT terminals in the BNSTdl express presynaptic corticotropin releasing factor (CRF) receptor type 2 (CRFR2). This suggests that CRFR2 might be involved in the modulation of OT release. To test this hypothesis, we measured OT content in microdialysates collected from the BNSTdl of freely-moving male Sprague-Dawley rats following the administration of a selective CRFR2 agonist (Urocortin 3) or antagonist (Astressin 2B, As2B). To determine if type 1 CRF receptors (CRFR1) are also involved, we used selective CRFR1 antagonist (NBI35965) as well as CRF, a putative ligand of both CRFR1 and CRFR2. All compounds were delivered directly into the BNSTdl via reverse dialysis. OT content in the microdialysates was measured with highly sensitive and selective radioimmunoassay. Blocking CRFR2 with As2B caused an increase in OT content in BNSTdl microdialysates, whereas CRFR2 activation by Urocortin 3 did not have an effect. The As2B-induced increase in OT release was blocked by application of the CRFR1 antagonist demonstrating that the effect was dependent on CRFR1 transmission. Interestingly, CRF alone caused a delayed increase in OT content in BNSTdl microdialysates, which was dependent on CRF2 but not CRF1 receptors. Our results suggest that members of the CRF peptide family modulate OT release in the BNSTdl via a fine-tuned mechanism that involves both CRFR1 and CRFR2. Further exploration of mechanisms by which endogenous OT system is modulated by CRF peptide family is needed to better understand the role of these neuropeptides in the regulation of anxiety and the stress response.